2020
DOI: 10.1111/ivb.12275
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mating on female reproduction across hermaphroditic freshwater snails

Abstract: Sexual conflicts often arise between mating partners because each sex tries to maximize its own reproductive success. One major male strategy to influence a partner's resource allocation is the transfer of accessory gland proteins. This has been shown to occur in simultaneous hermaphrodites as well as in organisms with separate sexes. Although accessory gland proteins affect the investment of resources in both male and female function, we here specifically focus on female investment. In the great pond snail, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 98 publications
(137 reference statements)
0
8
1
1
Order By: Relevance
“…Furthermore, the snails injected with seminal fluid from DE and F2 laid smaller eggs (Table 1, Figure 3b). In this assay, we did not detect an increase in egg size of the focal snails injected with seminal fluid from the laboratory strain, although this was expected based on indirect evidence from a previous study (Figure 3b, Swart et al., 2020). The R 2 value indicated that the fixed factor Population explained most variance in egg number, and also explained an approximately equal amount of variance in egg size, as did the random factor, Family (Table 1).…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…Furthermore, the snails injected with seminal fluid from DE and F2 laid smaller eggs (Table 1, Figure 3b). In this assay, we did not detect an increase in egg size of the focal snails injected with seminal fluid from the laboratory strain, although this was expected based on indirect evidence from a previous study (Figure 3b, Swart et al., 2020). The R 2 value indicated that the fixed factor Population explained most variance in egg number, and also explained an approximately equal amount of variance in egg size, as did the random factor, Family (Table 1).…”
Section: Resultscontrasting
confidence: 51%
“…We next conducted a bioassay to characterize variation in SFP functions among field populations. In brief, we intravaginally injected seminal fluids of selected families into standardized focal snails, and then assessed the reproductive performance of focals, in terms of both egg production and sperm transfer in subsequent matings, as reported in previous studies (Koene et al., 2010; Nakadera et al., 2014; Swart et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…O tamanho varia de 5 mm (Physidae) a 33,5cm de comprimento na espécie Triplofusus giganteus (Kiener, 1840) (TAYLOR, 2003;LYONS;LEE, 2018). A reprodução da classe é diversificada, mas normalmente são dioicos, ocorrendo hermafroditas (CASPERS, 1980;SCHÄRER;ARNQVIST, 2012;SWART et al, 2020).…”
Section: Classe Gastropoda Cuvier 1795unclassified